Purification assay to prepared ultrapure carboxymethyl-chitosan. Issue 9 (2nd September 2017) - Sheikholeslami, Zeinab Sadat; Imani, Mohammad; Atai, Mohammad; Nodehi, Azizollah; Salimi-Kenari, Hamed
ABSTRACT: Carboxymethyl Chitosan (CMCh) is a semi-synthetic derivative of chitosan (a natural biopolymer) with increasing biomedical applications as a matrix or scaffold material for tissue engineering applications. Since, the presence of impurities can cause immunological reactions in vivo where ultimately pure materials are needed. To this end, purity of commercial-grade CMCh samples was investigated here along with their purification by a solvent/nonsolvent technique. The resulting polymer was characterized by differential scanning calorimetry (DSC), thermal gravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR) and energy dispersive X-ray spectroscopy (EDX) to confirm the validity of the purification process.